Attitudes towards telemedicine in ophthalmology: a population-based online survey in Germany - Fink, David; Holz, Frank G.; Finger, Robert P.; Terheyden, Jan H. (BMC health services research, 2025)
Despite the increasing impact of telemedicine services on global healthcare provision, little data on acceptance and preference for telemedicine services at the population level are available to date. This is especially important for telemedicine in ophthalmology, where commercial telemedical applications are regularly offered outside of the state-funded health care system. Our study investigates the acceptability of tele-ophthalmology to the German population and associated sociodemographic factors.
Gesehen am 29.10.2025